Enhanced Typing and Tracking of Methicillin-Resistant Staphylococcus aureus and Methicillin-Susceptible S. aureus in Irish Hospitals using Whole-Genome Sequencing - EARLS, MEGAN ROONEY (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) are a major cause of healthcare-associated and community-associated infection worldwide, with many clones having achieved pandemic status. The development of high-throughput whole-genome sequencing (WGS) has provided the enhanced resolution required to accurately track the spread of MRSA in order to inform more effective infection prevention and control strategies. This technology has also revolutionised investigations of the evolution of established and emerging clones. The work described in this thesis used a variety WGS approaches to comprehensively investigate MRSA isolates from two protracted outbreaks in Irish hospitals and characterised the isolates in relation to international MRSA. The work also used WGS to investigate the transmission dynamics of S. aureus among healthcare workers (HCWs) and patients in a large Dublin hospital. The first part of the study investigated Panton-Valentine leukocidin (PVL)-negative CC1-ST1MRSA-IV, exhibiting high-level mupirocin-resistance (MupR) mediated by an ileS2-encoding conjugative plasmid, recovered from a protracted outbreak in a large Dublin hospital (H1) between 2013 and 2016. The study aimed to (i) characterise the ileS2-encoding plasmid, (ii) confirm/dispute a single clonal outbreak and (iii) investigate the relatedness of outbreak isolates to other PVL-negative ST1-MRSA-IV in Ireland. A total of 89 ST1-MRSA-IV isolates from patients (n = 85), HCWs (n = 3) and the environment (n = 1) were investigated. All isolates underwent Illumina MiSeq WGS, DNA microarray profiling and antimicrobial susceptibility testing. The vast majority (78/89) of isolates grouped into one major core-genome multilocus sequence typing (cgMLST)-based minimum spanning tree (MST) cluster, which included two sub-clusters (I and II). Sub-cluster I consisted of 57 isolates with an average of 25 pairwise allelic differences. This included 43/46 H1 isolates, 10/32 isolates from six other healthcare facilities (HCFs) and 4/11 community isolates, all of which were multidrug-resistant (MDR) and 50/57 of which were MupR. The 46 kb ileS2-encoding plasmid characterised also harboured qacA. Two HCW isolates from sub-cluster I differed from the remaining sub-cluster I isolates by 12-53 pairwise single nucleotide variations (SNVs). Sub-cluster II consisted of 21 isolates with an average of 61 pairwise allelic differences. This included 3/46 H1 isolates, 13/32 isolates from nine other HCFs and 5/11 community isolates, the majority (19/21) of which were MDR. These results identified the outbreak strain in seven HCFs and showed that it constitutes a MupR variant of the predominant ST1-MRSA-IV clone in Ireland. The plasmid-encoded ileS2 (encoding MupR) and qacA (encoding chlorhexidine resistance) genes in the outbreak isolates very likely contributed to maintenance of the outbreak as both mupirocin and chlorhexidine are used routinely for MRSA decolonisation. The MDR CC1-ST1-MRSA-IV clone identified from the outbreak did not match the characteristics of the only other previously defined PVL-negative ST1-MRSA-IV clone, known as WA MRSA-1. The second part of this study used WGS to investigate the origin of the clone, to determine whether it constitutes a MDR sub-clone of WA MRSA-1 or a distinct, yet uncharacterised, PVL-negative ST1-MRSA-IV clone. Ten CC1-MSSA and 139 CC1-MRSA-IV Irish isolates recovered between 2004 and 2017 (including 89 isolates from the previous part of the study) were investigated. These were compared to 21 German CC1MRSA, 10 Romanian CC1-MSSA, 10 Romanian CC1-MRSA and two UAE CC1-MRSA, which were selected from an extensive global database, based on similar DNA microarray profiles to the Irish isolates. All isolates underwent Illumina MiSeq WGS and core-genome (cg)SNV analysis. Two PVL-negative clades (A and B1) were identified among four main clades. Clade A included 20 German isolates, 34 Irish isolates, and all Romanian MRSA and MSSA isolates, the latter of which differed from clade A MRSA by 47–130 cgSNVs. Clade B1 included the remaining German isolate, 17 Irish isolates and the two UAE isolates, all of which corresponded to the WA MRSA-1 clone based on genotypic characteristics. MRSA within clades A and B1 differed by 188 cgSNVs and clade-specific SCCmec characteristics were identified, indicating independent acquisition of SCCmec. These results identified a European PVL-negative CC1-MRSA-IV clone that is distinctly different from WA MRSA-1, and which may have originated in South-Eastern Europe. From 2009 to 2011 (transmission period [TP] 1) and 2014 to 2017 (TP2), two outbreaks involving CC88-MRSA spa types t186 and t786, respectively, occurred in the neonatal intensive care unit (NICU) of an Irish hospital. The third part of this study used WGS to investigate the relatedness of these isolates, their relatedness to other CC88 MRSA in Ireland, and their likely geographic origin. A total of 28 Irish CC88MRSA isolates recovered between 2009 and 2017 were investigated, including 20 patient and two HCW isolates from the outbreak hospital, and six patient isolates from four other hospitals. These were compared to 13 international isolates, selected from an extensive global database based on similar DNA microarray profiles to the Irish isolates. The majority (25/28) of Irish isolates (including those from the outbreak hospital and two additional hospitals) were identified as ST78-MRSA-IVa and formed a large cluster, exhibiting 1–71 pairwise allelic differences, in a whole-genome (wg)MLST-based MST. The TP2 isolates were characterised by a different spa type and the loss of hsdS. The three remaining Irish isolates were identified as ST88MRSA-IVa and dispersed at the opposite end of the MST, exhibiting 81–211 pairwise allelic differences. Core-genome MLST and sequence-based plasmid analysis revealed the recent shared ancestry of Irish and Australian ST78-MRSA-IVa, and of Irish and French/Egyptian ST88-MRSA-IVa. These results revealed the homogeneity of isolates from the two NICU outbreaks, HCW involvement in the outbreak and the presence of the outbreak strain in two other Irish hospitals. HCWs have been repeatedly linked to S. aureus outbreaks, however, routine HCW screening for MRSA is not performed in Irish hospitals. The aim of the fourth part of this study was to use WGS to investigate whether HCWs are a significant source of S. aureus in patients in non-outbreak scenarios. Additionally, as the rate of MSSA among S. aureus causing invasive infections in Ireland is increasing, the secondary aim of this study was to investigate the S. aureus (MSSA and MRSA) population in a large Dublin hospital, using WGS. Oral and nasal samples from patients and HCWs, and clinical S. aureus isolates, were collected on nine wards of an Irish hospital over six months. Near-patient environmental and air sampling was also performed. MRSA and MSSA were detected using SASelect/MRSASelect chromogenic agars and routine identification methods. All isolates underwent Illumina MiSeq WGS. Staphylococcus aureus was recovered from 35.6% of HCWs, 22.7% of patients, 15.2% of near-patient areas and 20.7% of air sampling sites. MRSA was recovered from 3.4% of HCWs, 1.5% of patients, 0% of near-patient areas and 6.0% of air sampling sites. The ST45 (16.1%), ST30 (14.9%) and ST5 (11.5%) lineages were particulary prevalent among both patients and HCWs. Based on wgMLST, 15 transmission cases were identified involving ~35% of all isolates investigated. A total of 3/30 S. aureus-positive patients harboured a strain closely related to that of a HCW, and 3/53 S. aureus-positive HCWs harboured a strain closely related to that of a patient. These results indicated that HCWs rarely transmit S. aureus to patients in non-outbreak settings, suggesting that routine screening of HCWs for MRSA may not be benefical in MRSA-endemic settings. This study used WGS to detect and characterise a MDR MRSA clone emerging in Europe, investigate two protracted MRSA outbreaks, identify a novel ileS2 and qacA-encoding plasmid and elucidate the transmission dynamics of S. aureus in a large Dublin hospital. Harmonised efforts must be made to facilitate the widespread establishment of WGS technologies in surveillance and clinical microbiology laboratories so that they may be used to directly benefit public health and patient care in real-time.
APPROVED
Keywords: Staphylococcus aureus (MRSA); MRSA